Probody Therapeutics: An Emerging Class of Therapies Designed to Enhance On-Target Effects with Reduced Off-Tumor Toxicity for Use in Immuno-Oncology - Autio, Karen A; Boni, Valentina; Humphrey, Rachel W; Naing, Aung (Clinical cancer research, 2020)
The deep and durable antitumor effects of antibody-based immunotherapies such as immune checkpoint inhibitors (ICIs) have revolutionized oncology and transformed the therapeutic landscape for many cancers. Several anti-programmed death receptor 1 and anti-programmed death receptor ligand 1 antibodies have been approved for use in advanced solid tumors, including melanoma, non-small cell lung cancer, bladder cancer, and other cancers. ICIs are under development across many tumor types and preliminary results are compelling. However, ICIs have been associated with severe immune-related adverse events (irAEs), including rash, diarrhea, colitis, hypophysitis, hepatotoxicity, and hypothyroidism, which in some cases lead to high morbidity, are potentially life-threatening, and limit the duration of treatment. The incidence of severe irAEs increases further when programmed cell death-1 and programmed cell death ligand-1 inhibitors are combined with anti-CTLA-4 and/or other multidrug regimens. Probody therapeutics, a new class of recombinant, proteolytically activated antibody prodrugs are in early development and are designed to exploit the hallmark of dysregulation of tumor protease activity to deliver their therapeutic effects within the tumor microenvironment (TME) rather than peripheral tissue. TME targeting, rather than systemic targeting, may reduce irAEs in tissues distant from the tumor. Probody therapeutic technology has been applied to multiple antibody formats, including immunotherapies, Probody drug conjugates, and T-cell-redirecting bispecific Probody therapeutics. In preclinical models, Probody therapeutics have consistently maintained anticancer activity with improved safety in animals compared with the non-Probody parent antibody. In the clinical setting, Probody therapeutics may expand or create therapeutic windows for anticancer therapies.